Impact of Total Quality Management on Organizational Learning among Nigerian SMEs: The Moderating Role of Strategic Thinking - Adelakun, Christo Gbenga; Olaleye, Banji Rildwan; Khumalo, Ntseliseng; Omikunle, Yinka Emmanuel (Acta Universitatis Danubius. Œconomica, 2025)
Organizational learning (OL) has become a vital capability for staying competitive in the 21st-century business world. This research examines the impact of Total Quality Management (TQM) on organizational learning in small and medium-sized enterprises (SMEs) in Nigeria, while also considering the moderating influence of strategic thinking. Data collected from survey responses of 154 SME owners in Ejigbo Local Government Area, Osun State, were analyzed using partial least squares structural equation modeling (PLS-SEM) to test the proposed relationships. The findings indicate that TQM significantly improves organizational learning (β = 0.251, t = 2.741) and that strategic thinking further enhances this link (β = 0.287, t = 2.382). These results expand organizational learning theory by positioning TQM as both an operational and strategic facilitator of learning, while also emphasizing the cognitive function of strategic thinking in amplifying learning outcomes. Practically, the research highlights the importance for SME managers to implement TQM practices and foster forward-thinking skills to promote adaptability, innovation, and competitiveness. Policymakers and development agencies are encouraged to develop initiatives that integrate quality management with strategic thinking training to enhance SME resilience. Limitations related to the cross-sectional design, sample scope, and reliance on self-reported data are acknowledged. Suggestions for future research include longitudinal studies, cross-country comparisons, and the integration of digital transformation factors. Overall, the study demonstrates that combining TQM with strategic thinking offers SMEs a powerful pathway toward becoming learning organizations capable of thriving in dynamic environments.